The Role of the Reverse Fault on the Permeability Evolution in Mining Coal. (11th August 2021) - Zhou, Rui; Qin, Yujin; Hu, Yang
Abstract : To prevent and control the coal seam gas disaster affected by the reverse fault, we performed gas seepage tests, which consider stress-loading and unloading schemes, to investigate the stress change and coal permeability of the mining coal with reverse fault. The experimental results show that the mechanical behavior and permeability change of the mining coal are related to the distance between the coal and the reverse fault. The stress concentration coefficient of the coal body gradually increases. The closer is the distance between the coal and the reverse fault, the larger are the deviatoric stress peak and strain. In comparison with the coal sample M1 that is 5 m away from the reverse fault, the deviatoric stress peak and axial strain of the coal sample M3, 35 m away from the reverse fault, increase by 40.74% and 26.73%, respectively. In this stage, the permeability of M1, M2, and M3 coal samples increases by 22.1%, 28.0%, and 36.7%, respectively. In another stage, the stress concentration coefficient of coal increases to the peak and then decreases, causing the deviatoric stress peak and strain of coal to rise first and then fall. In comparison with the coal sample M4 that is 65 m away from the reverse fault, the deviatoric stress peak and axial strain of coal sample M6, 5 m away from the reverse fault, decrease by 29.48% and 5.55%, respectively. The permeability of coal samples M4, M5, and M6 increases by 23.6%, 37.2%, and 20.8%, respectively. Based on the gas seepage test results, we established the permeability model of mining-induced coal under the influence of a reverse fault, with consideration of the volume changes of coal fractures induced by adsorption and desorption. In the model, the variations of permeability in both stages of the prepeak and postpeak were deduced, which was verified with the experimental data. The verification results demonstrate that the proposed model has the capacity to predict the permeability evolution of mining coal under the influence of a reverse fault.